2021
DOI: 10.1111/tbed.14400
|View full text |Cite
|
Sign up to set email alerts
|

Porcine circovirus‐2 in Africa: Identification of continent‐specific clusters and evidence of independent viral introductions from Europe, North America and Asia

Abstract: Porcine circovirus‐2 (PCV‐2) is associated with several disease syndromes in domestic pigs that have a significant impact on global pig production and health. Currently, little is known about the status of PCV‐2 in Africa. In this study, a total of 408 archived DNA samples collected from pigs in Burkina Faso, Cameroon, Cape Verde, Ethiopia, the Democratic Republic of the Congo, Mozambique, Nigeria, Senegal, Tanzania and Zambia between 2000 and 2018 were screened by PCR for the presence of PCV‐2. Positive ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
3
7
1
Order By: Relevance
“…Similarly, Asia and China in particular, have played an increasing role in African countries’ economies [ 34 ], including the agricultural sector, thus increasing the risk of direct or indirect contact between animals and their by-products. Similar connections have been reported for several infections affecting both companion animals and livestock [ 35 , 36 ]. The high environmental resistance of PPV1 could also point to more obscure, indirect, and long-distance transmission pathways.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, Asia and China in particular, have played an increasing role in African countries’ economies [ 34 ], including the agricultural sector, thus increasing the risk of direct or indirect contact between animals and their by-products. Similar connections have been reported for several infections affecting both companion animals and livestock [ 35 , 36 ]. The high environmental resistance of PPV1 could also point to more obscure, indirect, and long-distance transmission pathways.…”
Section: Discussionsupporting
confidence: 83%
“…a lower virulence, were also involved remains to be established. A previous study reported the detection of PCV2a and PCV2b genotypes in Ethiopia [ 10 ]; unfortunately, the low viral titer hindered the sequencing of all positive samples. In one of the sequenced samples, the presence of PCV2b was confirmed, while the other 4 sequences were classified as PCV2d, further demonstrating the breadth of genetic heterogeneity featuring Ethiopian molecular epidemiology.…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study estimated a likely PCV2b introduction in Ethiopia from Asia [ 10 ]. Therefore, a similar importation pathway could be expected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations